A fabricação do ferro no começo do século XIX em Ipanema no período de Hedberg e Varnhagen - Pizol, Helton de Bernardi (2009)
The present dissertation is inserted in the History of Science in Brazil , in the metalurgy field and its institutionalization in Brazil. The focus of the research is Fazenda Ipanema, located in Araçoiaba da Serra, state of São Paulo, where since the 16 th century there have been attempts, achievements and abortions in the production of iron. From the 18 th century to 19 th century, a Chemist ,John Manso Pereira , was sent to Ipanema during the first endeavor from the government to establish an ironworks factory at the place. The project was only achieved with the arrival of the swedish Hedberg, in the beginning of the 19th century,with a group of workers. Hedberg worked until 1814 when he was dismissed and replaced by the german Friedrich Ludwig Wilhelm Varnhagen. This dissertation is about the attempts to establish an iron and steel industry until Varnagen's return to Germany After this period, there were a few fruitless attempts during the 19th century and first half the 20th, with Fazenda Ipanema becoming nowadays an ambiental area preserved by IBAMA.( Brazilian Institute of Environment and Renewable Natural Resources)